Odpowiedzi

Najlepsza Odpowiedź!
2010-03-13T13:20:01+01:00
A)P=abx /:ab
x=P/ab

b) R=ax/(kreska ułamkowa) b /* b
Rb=ax /: a
x= Rb/a

c) S=a/bx /*x
Sx=a/b /:S
x= a/bS

d) T=1/abx /* x
Tx= 1/ab /: T
x= 1/abT

e) y=2t-3x /: (2t-3)
x= y/2t-3

f) y=2(x-1)
y=2x-2
-2x=-2-y /:(-2)
x= 1+y/2

g) y=x-1/2
-x=-1/2-y /: (-1)
x= 1/2+y

h) y=2/x-1 /* x-1
yx- y= 2
yx=2+y/:y
x= 2+y/y

i) P=1/3(a²+2ax)
P= 1/3a² + 2/3ax
-2/3ax= a²-P/3 /* (-3a/2)
x= -(a³-P)/2
2 5 2
2010-03-13T13:35:37+01:00
A)P=abx
P/ab=x
b)R=ax(kreska ułamkowa)/razy b
P*b=ax/(podzielone)a
Pb=x
c)S=a(kreska ułamkowa)bx/podzielone b
Rb=a (kreska ułamkowa) x/ podzielone a
Rb (kreska ułamkowa) a=x
d)T=1(kreska ułamkowa) abx/ podzielone ab
Tab=1(kreska ułamkowa) x/podzielone 1
Tabx=1/podzielona x
1 (kreska ułamkowa) Tab=x
e)y=2t-3x/plus 3x
y+3x=2t/podzielone 2
y-3 (kreska ułamkowa) 1 =x
f)y=2(x-1)/plus 2
y+2=2x/podzielone 2
y+2 (kreska ułamkowa)=x
g)y=x-1(kreska ułamkowa)2/razy 2
2y=x-1/plus1
1+2y=x
h)y=2(kreska ułamkowa)x-1/(x-1)
y(x-1)=2/podzielone y
x-1=2 (kreska ułamkowa)y/plus1
x= 2 (kreska ułamkoway)/ plus1
i)1/3(a2(kwadrat)+2ax)/razy3
3p=a (kwadrat) +2ax/minus a (kwadrat)
3p-a (kwadrat)=2ax/podzielone 2a
3p- a (kwadrat) (kreska ułamkowa) 2a=x


1 5 1